THE INFLUENCE OF BUILDING ENVELOPES TOWARDS INDOOR CLASSROOM TEMPERATURE (Case: BINUS Alam Sutera Campus) - Rivanus Dewanto (International Journal on Livable Space, 2019)
ABSTRACTThe building façade of BINUS Alam Sutera campus is designed with wall variations of building envelope both in terms of material use and of openings volume. These conditions encourage the researcher to observe how much the indoor temperature difference in the classroom is correlated to the wall completion of the building envelope. The method used was by measuring indoor and outdoor temperatures at the same time periods (morning, midday, and afternoon) from the classrooms in different floors. The result of the study reveals that indoor temperature increases relatively towards the sun orientation of north-northeast and of west-southwest. The building envelope with precast concrete and window-wall affects indoor temperature relatively higher in the morning and lower in the afternoon. Whereas the building envelope with precast concrete of dead-glass variation affects indoor temperature relatively lower in the morning yet higher in the afternoon.Keywords: Building envelopes, indoor temperature, classrooms